Peningkatan Kompetensi Guru Melalui Pelatihan Perancangan Soal Berbasis Komputer - Rochmawati Rochmawati; Susanti Susanti; Agung Listiadi; Eko Wahjudi; Suci Rohayati (IKIP PGRI Bojonegoro, 2019)
ABSTACTA teacher should be updating IT currently is already widely used, one of which is the designing problems based IT at school in this regard problems online. The purpose of this training is to know how the implementation of the training design tool evaluation software with quis creator for teachers MGMP Se-Sidoarjo; and to conduct an evaluation of the implementation of the training software quis creator. This training method using direct instruction. The results showed that the implementation of the training training evaluation tool design software quis creator for teachers MGMP Sidoarjo is going well and according to the schedule already agreed. In total there are four activities followed by participants in a series of training activities. Training activities include the introduction of an application in the evaluation of learning, installation software advocates for problems such as subjects.; 2) Evaluation of implementation of training software quis creator, trainees feel happy and want advanced training. Keywords: IT, software training, reserved online ABSTRAKSeorang guru harus mengupdate IT yang saat ini sudah banyak digunakan, salah satunya adalah merancang soal-soal yang berbasis IT di sekolah dalam hal ini soal-soal online. Tujuan pelatihan ini adalah untuk mengetahui bagaimana pelaksanaan pelatihan perancangan alat evaluasi dengan software quis creator bagi guru-guru MGMP Se-Sidoarjo; dan untuk melakukan evaluasi pelaksanaan pelatihan software quis creator . Pelatihan ini menggunakan metode direct instruction. Hasil pelatihan menunjukkan bahwa pelaksanaan pelatihan perancangan alat evaluasi software quis creator bagi guru-guru MGMP Se-Sidoarjo berjalan dengan baik dan sesuai dengan jadwal yang sudah disepakati. Secara keseluruhan terdapat empat kegiatan yang diikuti oleh peserta dalam rangkaian kegiatan pelatihan ini. Kegiatan pelatihan antara lain pengenalan aplikasi dalam evaluasi pembelajaran, penginstallan software pendukung untuk soal-soal mata pelajaran.; 2) Evaluasi Pelaksanaan Pelatihan software quis creator, peserta pelatihan merasa senang dan menginginkan pelatihan lanjutan. Kata kunci: IT, pelatihan software, soal online